The Effectiveness of Breathing and Relaxation Techniques on Somatic Tension and Trait Anger - Nejatifar, Sara; Faramarzi, Salar (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to evaluate the effectiveness of a structured breathing and relaxation intervention in reducing somatic tension and trait anger among Canadian adults. A randomized controlled trial was conducted with 30 participants (15 intervention, 15 control) recruited from community and educational centers in Isfahan, Iran. The intervention group underwent ten 60-minute sessions over five weeks, incorporating diaphragmatic breathing, progressive muscle relaxation, and guided imagery techniques. Assessments were conducted at pre-test, post-test, and five-month follow-up using the Pennebaker Inventory of Limbic Languidness (Muscle Tension Subscale) and the State-Trait Anger Expression Inventory-2 (STAXI-2). Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests via SPSS-27. Significant main effects of time and group, as well as time × group interactions, were found for both somatic tension (F(2,56) = 36.71, p < .001, η² = .58) and trait anger (F(2,56) = 27.43, p < .001, η² = .49). Post-hoc comparisons revealed a significant reduction in somatic tension from pre-test to post-test (MD = 9.62, p < .001) and from pre-test to follow-up (MD = 11.79, p < .001). Trait anger also decreased significantly between pre-test and post-test (MD = 6.12, p < .001), and between pre-test and follow-up (MD = 6.95, p < .001), with sustained effects over time. Breathing and relaxation techniques are effective in reducing both somatic and emotional symptoms, with benefits persisting up to five months post-intervention. These findings support the integration of psychophysiological self-regulation practices into mental health and stress management programs as non-invasive and cost-effective strategies.